Introduction to a discussion on the third cohesion report: Policy-relevant research and research-relevant policy - Christer Bengs (European Journal of Spatial Development, 2004)
The two categories of academic and applied research seem to be the concrete token of an increased intermingling between the world of politics and that of science. In this unholy alliance, the money-power is pushing for policy-relevance while researchers struggle for their academic credibility. In what follows, these dramas will be commented upon as will the newly issued third cohesion report from  the European Commission. Though the current situation may seem confusing the only way to sort things out is to grab the bull by its horns and start a discussion.